JY61 IMU sensor external validity: a framework for advanced pedometer algorithm personalisation - Bacic, B.; Feng, C.; Li, W. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This case study aims to compare a low-cost inertial sensor prototype (JY61 IMU + ESP8266 MCU designed for real-time non-proprietary data streaming over Wi-Fi) with a high-end mobile (iPhone 13 Pro Max) using Matlab pedometer algorithm. Preliminary experiments used data collected at 100 Hz including 20, 50, and 100 steps on a partially carpeted and partially hard floor surface with the test subject wearing high heels and tennis shoes. The error comparison between the sensor (0-1%) and high-end mobile (0-2%) suggests that the sensor can be used as a privacy-preserving pedometer which is smaller, lighter and a low-cost alternative to mobile sensors. The experimental framework developed for advanced pedometer personalisation is applicable in education, gate pattern analysis and other sensor advancements for sport equipment and wearable technology applications.